The Hubungan Karakteristik Perawat dengan Kemampuan Berpikir Kritis dalam Merawat Pasien Gangguan Jiwa dengan Komorbid di RSJ Dr. Radjiman Wediodiningrat Lawang: Hubungan Karakteristik Perawat Dengan Kemampuan Berpikir Kritis Dalam Merawat Pasien Gangguan Jiwa Dengan Komorbid - Yunita - Fitrianingrum; Suryanto Suryanto; Renny Nova (Jurnal Keperawatan Terapan, 2025)
Mental disorders with comorbidities are complex, chronic, and debilitating conditions that lead to complications. Critical thinking ability play an important role in caring for mental disorder patients with comorbidities to resolve complex situations and ensure continuity of care provided. The characteristics of nurses are likely influenced by their critical thinking skills. This study aims to determine the relationship between nurse characteristics and critical thinking skills in caring for mental disorder patients with comorbidities at RSJ Dr. Radjiman Wediodiningrat Lawang. This correlation research employs a cross sectional study approach, with a total of 35 nurses who work in the Physical Inpatient Room (B). The instrument used in this research was a questionnaire. Based on the results of bivariate analysis using non-parametric Spearman rank test, it was found that the characteristics of age, gender, education, employment status, marital status and training had no relationship with critical thinking abilities. The characteristics of work experience have a significant relationship with critical thinking abilities, and the strength of the relationship is moderate, while the direction of the relationship is negative. For future researchers, to be able to research other factors that influence critical thinking skills in clinical nurses by using different research approaches or instruments.